PENGEMBANGAN BAHAN AJAR IPS BERBASIS KONSTRUKTIVISTIK UNTUK SEKOLAH DASAR - Lestari, Megayani (Perspektif Ilmu Pendidikan, 2016)
The purpose of this research is to produce the learning materials for Social Science Study at the fifth grade of elementary school students. The materials were focused on the theme of the Indonesian struggle against Dutch and Japanese colonialism. The learning materials were produced by applying the research and development model adopted by Atwi Suparman. This research, conducted as from October 2015 through 2016, involved 43 students of the fifth grade, in the State Primary School of Jati 03 Pag,i East Jakarta. For product evaluation, this research used expert review before trying out to-one-to-one, small group, and field test. The try out indicates, the learning materials developed for Social Science Study based on constructivism meets the criteria of â€œvery goodâ€ at the fifth grade of Primary School.